1993
DOI: 10.2169/internalmedicine.32.530
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Painful Lymphadenopathy in Extracranial or Systemic Infection: Etiology of New Daily Persistant Headaches.

Abstract: From 108 cases of new daily persistent headaches, clinical or laboratory evidence was found suggesting extracranial or systemic infections in: 28 cases (25.9%) of gastrointestinal mainly Salmonella, 28 (25.9%) urinary Coli, 16 (14.8%) Streptococcal, 4 (3.7%) each ofEpstein Barr virus or Toxoplasma, and 1 (0.9%) each of Herpes Zoster or pneumonia. A group of26 (24.1%) showed high Proteus OXtiter or clinical adenoviral involvement. All had normal neurological examinations plus selective negative neuroimaging or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 5 publications
(1 reference statement)
0
33
0
2
Order By: Relevance
“…However, up to 40% of their patients did not have a known trigger. In addition to the risk factors previously mentioned, the transformation of an episodic headache into a chronic headache (or the onset of NDPH) in adults has also been associated with hypothyroidism, hypertension, consumption of alcohol more than 3 times per week, analgesic overuse, daily consumption of caffeine [15], multiple types of infections [16], and stressful life events [17]. A particularly interesting observation is that many patients will wake up after extracranial surgery (such as an appendectomy) with NDPH [13,18,19].…”
Section: Ndph Occurs More Frequently In Young Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, up to 40% of their patients did not have a known trigger. In addition to the risk factors previously mentioned, the transformation of an episodic headache into a chronic headache (or the onset of NDPH) in adults has also been associated with hypothyroidism, hypertension, consumption of alcohol more than 3 times per week, analgesic overuse, daily consumption of caffeine [15], multiple types of infections [16], and stressful life events [17]. A particularly interesting observation is that many patients will wake up after extracranial surgery (such as an appendectomy) with NDPH [13,18,19].…”
Section: Ndph Occurs More Frequently In Young Patientsmentioning
confidence: 99%
“…Diaz-Mitoma et al [20] noted that 84% of patients with NDPH had evidence of "active" EpsteinBarr virus infection. However, other infections can also provoke NDPH [16], and 43% of the patients in the childhood NDPH study reported some type of infection at the onset of symptoms [13]. Meineri et al [18] reported NDPH associated with recent seroconversion to herpes simplex virus or cytomegalovirus.…”
Section: Ndph Occurs More Frequently In Young Patientsmentioning
confidence: 99%
“…It is more common in females, with the female/male ratio in adults at 2.5:1 [5] and in children and adolescents at 1.8:1 [4•]. It has an earlier age of onset in women (ages [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] than in men (ages 26-45) [5]. One study of 680 pediatric headache clinic patients reported 189 (28%) with tension-type headache, 34 of whom met NDPH criteria [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…The pathophysiology of NDPH is unknown, although some general associations have been made with infection, extracranial surgery, stressful life events, hypothyroidism, hypertension, analgesic overuse, and frequent caffeine use [5,[19][20][21]. In one study of 34 pediatric headache patients with NDPH, five (15%) had a preceding infection, five (15%) had a preceding mild to moderate head injury, and four had significant psychosocial issues [7].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation